Sleep, recovery, and performance: The new frontier in high-performance athletics - Samuels, C. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
The relationship of sleep to post-exercise recovery (PER) and athletic performance is a topic of great interest because of the growing body of scientific evidence confirming a link between critical sleep factors, cognitive processes, and metabolic function. Sleep restriction (sleep deprivation), sleep disturbance (poor sleep quality), and circadian rhythm disturbance (jet lag) are the key sleep factors that affect the overall restorative quality of the sleep state. This article discusses these theoretic concepts, presents relevant clinical cases, and reviews pilot data exploring the prevalence of sleep disturbance in two groups of high-performance athletes.